Stratigraphy, sedimentology, and archaeology of Middle Pleistocene localities near Ceprano, Campogrande area, Italy. Issue 1 (January 2020) - Biddittu, Italo; Moncel, Marie-Hélène; Milli, Salvatore; Bellucci, Luca; Ruffo, Massimo; Saracino, Barbara; Manzi, Giorgio
Abstract: The Ceprano human calvarium, dated around 400, 000 yr, is a well-known fossil specimen. It represents significant evidence of hominin presence in the Italian peninsula during the Middle Pleistocene and may be considered representative of an archaic variant of the widespread and polymorphic species Homo heidelbergensis . Since its discovery (March 1994), systematic surveys in the Campogrande area near Ceprano, central Italy, identified 12 localities (CG1-12) with archaeological and/or paleontological assemblages. On this basis, fieldwork was carried out at Campogrande between 2001 and 2006, including drilled cores and excavations, allowing a detailed description of the stratigraphic and paleoenvironmental context associated with the human fossil specimen and the archaeological materials. In the present paper we focus on the stratigraphy and sedimentological features of the uppermost deposits, coupled with a detailed appraisal of the available lithic assemblages that mostly belongs to overlying sediments (CG9 and CG10 localities). We conclude that the Ceprano hominin died in a floodplain environment with a low topographic gradient, where a fluvial meandering channel occurred. The archaeological materials describe a network of sites that document common behavioural features of human groups of the mid-to-late Middle Pleistocene, representing evidence of the regionalization observed across Europe after Marine Oxygen Isotope Stage 12.